La ambientación física del aula en el proceso de aprendizaje en los niños del primer año de educación básica general de la Escuela Manuel de Echeandia de la ciudad de Guaranda provincia Bolívar – Ecuador durante el año lectivo 2011 2012 - Villena Camacho, Anita Virginia (2012)
The present Work of Grade allows to know the diverse forms that he/she should take into account to the moment to organize the classroom, the main ones characteristic that constitute it, the resources that should take into account to be able to carry out a good work. In the theoretical mark he/she took different authors' references that allow to deepen the problem and to assimilate the approaches emitted by them in their moment with their knowledge and in their spaces to be applied in other contexts with the experience and the investigator's so much capacity as of the State University of Bolívar in their group as contribution for the solution of this problem. The Atmosphere of the classroom in the process of the learning tries to give the appropriate place where the children developing the potential of the knowledge in the first years of its beginning of the high school with an eye toward the future in the person's integral formation in if in l family and for ended in the society. Where we will speak of different points that are very important that we should not leave aside like it tries in that an atmosphere where the physical area of the room should be appropriately orderly specifying each one of the places and corners with its respective working materials; to facilitate the boy to identify in that area to locate a working tool according to the necessities that in its moment the aerate, this will allow to act an efficient and effective education. Today in day is of great importance to have a good physical space since in the classroom of this it depends it will be since the impact that has this in the process of learning of the nines/as, of this of which it depends that they have a good motivation to carry out its knowledge, the atmosphere should be a great attractiveness that which will constitute a serene and warm atmosphere so that it XIII can develop a good learning since if the is not motivated and agusto in its working place won't have an effective learning. Since they will be the main beneficiaries when carrying out this work the offering them a more appropriate atmosphere in which you/they can be attracted it stops this way to achieve the prospective learning’s; it won't also allow only the number of children that you/they present indifference in the classroom on the physical atmospheres to diminish but rather they can also foment a better adaptation to the atmosphere of the school where he/she is carried out the activities which is characterized in having material; furniture, decoration and objects